Organización Contable al Almacén de Repuestos “Tituana Maldonado María Lourdes” de la ciudad de Loja, período del 01 de abril al 30 de junio del 2022. - Silva Naranjo, Thalia Salomé (2023)
This following research titled ACCOUNTING ORGANIZATION TO THE “TITUANA MALDONADO MARÍA LOURDES” PARTS WAREHOUSE OF THE CITY OF LOJA, PERIOD FROM APRIL 1st TO JUNE 30th, 2022, was carried out with the purpose of providing the owner with information about the situation economic and financial aspects of your business for correct decision-making, it is also done as a prerequisite for obtaining the Degree and Title of Engineer in Accounting and Auditing CPA. It began by preparing the chart of accounts according to its economic activity, which is made up of accounts and subaccounts in an orderly manner and with their respective code; In this way, the accounts manual was also made, which contains the description of each of the accounts, their movement and their balance, facilitating the application of the accounting process. Then, through the physical verification, the initial inventory was prepared in order to know the values, assets, rights, and obligations that the company possesses, an activity in which it was determined that in total assets it has a value of $ 252,365.71, total liabilities of $16,714.21 and its equity of $235,651.50 and, based on this, the Initial Balance Sheet was built. Auxiliary books were designed and prepared that simplified the operations at the time of their registration in the daily book such as auxiliary purchase, sales, documents receivable, and documents payable, in which through the source documentation the registration proceeded chronologically of the operations, whose results were registered in the main accounting books with which the Financial Statements were obtained, highlighting that the Income Statement reflects a total income of $32,293.29; total costs of $4,017.72, giving a gross profit on sales of $28,275.57 and a total expense of $2,892.01; Regarding the Statement of Financial Position, it reflects that it has a total of $275,828.18 in assets, a total of $18,600.65 in liabilities, and a total of $57,227.53 in equity; Similarly, the Cash Flow Statement shows a total cash value of $5,791.59. Finally, a net profit for the year of $21,576.03 was obtained, which is a positive result for the company, which will allow the owner to acquire more merchandise, and improve the warehouse infrastructure, among others; For this reason, it is suggested to the owner to apply the proposed accounting organization that positively favors the economic and financial development of the company, since it constitutes a source of support for its owner to opt for provisional measures that benefit the growth of her business.